Multipliers of the Peruvian Economy 2002 - Torres-Zorrilla, Jorge (2009)
This article illustrates an application of the input-output model to estimate the multiplier effects of investments and exports of the Peruvian economy. One conclusion is that multipliers of services are greater than multipliers of industries while primary products exhibit intermediate multipliers. Another conclusion is that exports reflect a much higher multiplier effect than do investments. Employment and wage multipliers appear greater for service sectors than for modern exporting sectors, such as mining and metallurgy, and for modern urban sectors, such as electricity, insurance, construction, and beverages.